Creating and sustaining virtual language communities - Lomicka, Lara (Foreign language annals, 2020)
During Covid‐19, educators have been forced to quickly and creatively rethink teaching practices and the education of future generations. Community is a key consideration in reconceptualizing how the traditional classroom might function successfully in an online space. How does the virtual community of language learners interact with each other and with the instructor? What practices might enable the online community to bond, develop a sense of trust, feel comfortable sharing information, and set goals together? The development of a social presence in communities of language learners is crucial to maintaining a sense of connectedness in the virtual classroom. This article discusses why it is critical to establish a virtual language community and provides practical implications for creating virtual presence and engaging students in these virtual communities. The Challenge With the mandate for social distancing, many traditional face‐to‐face language classes have moved to remote platforms. Considering this change, how might the notion of the community be re‐envisioned in the language classroom? How might instructors create a virtual presence and engage students in online communities?